Anthropogenic impacts on the water chemistry of a transboundary river system in Southeast Asia - Duc A. Trinh; Nga T. Do; Virginia N. Panizzo; Suzanne McGowan; Jorge Salgado; Andy R.G. Large; Andrew C.G. Henderson; Thuy T. Vu (Journal of Asian Earth Sciences: X)
The Red River originating from Yunnan province, China is the second largest river in Vietnam in terms of length and discharge. Combination of water chemistry monitoring data of 4 years (2018–2022) from different sub-basins of the Red River (the Da, Lo, Thao, Tra Ly, and Day) with historical datasets indicates a decline in pH from 8.1 in 2000 to 7.7 in 2021, greater CO2 concentrations and a shift from waters naturally dominated by carbonate weathering to waters dominated by evaporite weathering. Such changes were most apparent in the delta area where heavy human activities have increased influxes of most dissolved chemicals, except SiO2. Evaporite weathering is particularly enhanced by mining and deforestation occurring in upstream regions of both China and Vietnam. Pyrite oxidation, alongside silicate weathering, is enhanced along the Red River Fault Zone but reduced in tributaries with a higher proportion of hydropower reservoirs. Longer water residence times in these large reservoirs (total volume > 2.7x1010 m3) located in the Da and Lo sub-basins have also increased primary productivity, leading to higher evasion/uptake of CO2 and SiO2, lower total dissolved solids (TDS), and higher pH. The total physical and chemical denudation rates of upstream mountain tributaries ranged between 0.107 ± 0.108 and 0.139 ± 0.137 mm yr−1, mainly due to reservoir implementation and instream aquatic biogeochemistry changes. Our findings demonstrate that anthropogenic activities are profound factors impacting the water chemistry of the Red River system.